Ascariasis as an Unexpected Cause of Acute Pancreatitis with Cholangitis: A Rare Case Report from Urban Area - Phisalprapa, Pochamana; Prachayakul, Varayu (JOP. Journal of the Pancreas, 2013)
Context Ascaris lumbricoides is one of the most common parasitic infestations of human gastrointestinal tract. This parasitic infestation might be asymptomatic and only few studies on extraintestinal ascariasis have been reported. Ascending cholangitis and acute pancreatitis as a result of the Ascaris lumbricoides migrating into the biliary system and pancreatic duct were very rare complications. Here, we presented a case report of biliary ascariasis induced acute pancreatitis with cholangitis without imaging supported in a patient coming from urban area. Case report A 33-year-old woman lives in Bangkok, urban area of Thailand. She presented with severe epigastric pain for one day. Her diagnosis was Ascaris lumbricoides induced acute pancreatitis accompanied with ascending cholangitis. The investigation results showed no eosinophilia and no ascaris eggs in stool examination. The abdominal computed tomography showed slightly common bile duct dilatation. The parasite was found during an endoscopic retrograde cholangiopancreatography performed. The cholangiography revealed a roundworm in common bile duct. The parasite was successfully removed by using an extraction balloon catheter and a snare. Microbiological examination of the parasite revealed a 22 cm long adult form of Ascaris lumbricoides. Conclusion Ascaris lumbricoides is the uncommon cause of biliary obstruction with complications. It is also a possible cause even in the patients who live in urban areas. Endoscopic removal is the treatment of choice in addition to antihelminthic medications. Image: An adult form of Ascaris lumbricoides after extraction from common bile duct.